1991
DOI: 10.1017/s0890037x00033844
|View full text |Cite
|
Sign up to set email alerts
|

Wheat (Triticum aestivum) Cultivar Tolerance and Italian Ryegrass (Lolium multiflorum) Control with Diclofop, BAY SMY 1500, and Metribuzin

Abstract: In the field, 14 soft red winter wheat cultivars responded differently to 1.1 kg ai ha–1diclofop, 1.7 kg ai ha–1BAY SMY 1500, and 0.42 kg ai ha–1metribuzin applied POST. Diclofop and metribuzin did not injure any cultivar more than 10% on a silty clay soil. However, BAY SMY 1500 injured ‘Pioneer 2551’ and ‘Coker 983’ 39 and 21%, respectively, in March. All other cultivars were injured less than 10% by BAY SMY 1500. Early injury did not translate into yield loss in the cultivar tolerance study. In an applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 15 publications
1
30
1
Order By: Relevance
“…In our case, the crop also showed excellent tolerance to both pre-mixes when applications were made at Z21-23 stages which represent the tillering stage of wheat, and may be attributed to the enhanced capacity of wheat plants to metabolise the herbicides at these stages (Das, 2014). The differential sensitivity of wheat to metribuzin applied at its different growth stages (Shaw & Wesley, 1991;Grey & Bridges, 2003) and different doses (Balyan, 1999) has been demonstrated earlier.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our case, the crop also showed excellent tolerance to both pre-mixes when applications were made at Z21-23 stages which represent the tillering stage of wheat, and may be attributed to the enhanced capacity of wheat plants to metabolise the herbicides at these stages (Das, 2014). The differential sensitivity of wheat to metribuzin applied at its different growth stages (Shaw & Wesley, 1991;Grey & Bridges, 2003) and different doses (Balyan, 1999) has been demonstrated earlier.…”
Section: Discussionmentioning
confidence: 80%
“…Dhawan et al (2010) and Kaur et al (2016) reported development of cross resistance in P. minor to pinoxaden in Punjab and Haryana states. Metribuzin is primarily a soil-residual herbicide, which can be applied post-emergence to wheat for the control of annual grasses and dicot weeds (Schroeder et al, 1986;Shaw & Wesley, 1991). Although metribuzin can control P. minor effectively, careful management, including timely application is required to achieve good crop tolerance and weed control (Runyan et al, 1982;Schroeder et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Injury from the early-spring metribuzin application was only temporary, probably due to rapid wheat growth during March, while injury from the fall application timings continued to be apparent months after application (Tables 2 and 3). Shaw and Wesley (1991) observed ≤6% injury for fourteen soft red wheat cultivars planted in silt clay soils when sprayed with metribuzin in early February. Higher levels of wheat injury were observed in a separate study conducted on sandy loam soils, and the authors attributed these differences to changes in the soil type.…”
Section: Resultsmentioning
confidence: 86%
“…While metribuzin can control Italian ryegrass effectively, careful management, including cultivar selection and timely application, is required to achieve acceptable crop tolerance and weed control. Many agronomically desirable, high-yielding wheat cultivars are sensitive to metribuzin and cannot be planted if metribuzin is to be applied and some cultivars are extremely sensitive [31][32][33]. Bromoxynil in wheat will control wild radish but is ineffective on Italian ryegrass.…”
Section: Photosystem II Herbicidesmentioning
confidence: 99%
“…Previous research indicated that metribuzin reduced yield demonstrating the risks growers take when using this herbicide for weed control [16,31,33].…”
Section: Crop Response and Weed Controlmentioning
confidence: 99%